Treatment of Infants and Children With SARS-CoV-2 Monoclonal Antibodies: A European Case Series. Issue 2 (21st November 2022) - Rau, Cornelius; Auer-Hackenberg, Lorenz; Deubzer, Hedwig E.; Schwabel, Elisabeth; Jaros, Maria; Diederichs, Antonia; Lehrnbecher, Thomas; Holm, Mette; von Linstow, Marie-Louise; Martin, Luise; Dinges, Sarah Svenja; Rothensteiner, Maria; et al.
Abstract : Background: Although severe COVID-19 in children is rare, those with certain pre-existing health conditions are more prone to severe disease. Monoclonal antibodies (mAbs) against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are potent antiviral agents that reduce adverse clinical outcomes in adults, but are commonly not approved for use in pediatric patients. Methods: We retrospectively evaluated mAb treatment in children <12 years of age or <40kg with SARS-CoV-2 infection between January 1, 2021, and March 7, 2022, in 12 tertiary care centers in 3 European countries. Results: We received data from 53 patients from Austria, Denmark and Germany. Median age was 5.4 years [0–13.8, interquartile range (IQR) = 6.2], and median body weight was 20 kg (3–50.1, IQR = 13). The most frequent SARS-CoV-2 variant in this study, if known, was Omicron, followed by Delta and Alpha. Pre-existing conditions included immunodeficiency, malignancy, hematologic disease, cardiac disease, chronic lung disease, chronic liver disease, kidney disease and diabetes. Forty-two patients received sotrovimab (79%), 9 casirivimab/imdevimab (17%) and 2 bamlanivimab (4%). All but 1 patient survived. Median duration of hospital stay was 3 days (0–56, IQR = 6). Seven patients required treatment in an intensive care unit, and 5 required high-flow nasal cannula treatment. Potential side effects included neutropenia (6/53, 11%), lymphopenia (3/53, 6%), nausea or vomiting (2/53, 4%), rise of alanine transaminase (1/53, 2%) and hypotonia (1/53, 2%). Conclusions: MAb treatment was well tolerated by children in this cohort.